Megestrol Acetate-Induced Symptomatic Hypogonadism in a Male Patient - Lubna Bashir Munshi; Yumiko Tsushima; Kwan Cheng; Maria Brito (Case Reports in Endocrinology)
The hypothalamic-pituitary-adrenal (HPA) axis and the hypothalamic-pituitary-gonadal (HPG) axis are very sensitive and can be affected by external factors like stress, starvation, and medication. Medication-induced suppression of these axes can cause adrenal insufficiency (AI) and hypogonadism. Exogenous glucocorticoid use is the most common cause of iatrogenic AI. Our aim is to bring attention to another broadly prescribed medication, megestrol acetate (MA), as the cause of suppression of both these axes. We report a case of symptomatic hypogonadism and asymptomatic AI in a male patient secondary to MA. The patient presented with decrease in testicular size and erectile dysfunction. His total testosterone and morning cortisol levels were low, but FH, LH, and TSH were normal. His pituitary MRI was unremarkable. Upon discontinuation of MA, the patient’s testosterone and cortisol levels normalized and his symptoms resolved. Hypogonadism and AI are known adverse effects of MA, but symptomatic hypogonadism as the primary manifestation has only been reported once in previous literature. Prolonged hypogonadism can lead to sarcopenia, depression, and osteoporosis, while asymptomatic AI carries the risk of becoming overt AI. Thus, heightened awareness of the impact of MA on both these axes is necessary.